The impact of six-week dihydrogen-pyrroloquinoline quinone supplementation on mitochondrial biomarkers, brain metabolism, and cognition in elderly individuals with mild cognitive impairment: a randomized controlled trial - Sonja Baltic; David Nedeljkovic; Nikola Todorovic; Marijana Ranisavljev; Darinka Korovljev; Jelena Cvejic; Jelena Ostojic; Tyler W. LeBaron; Judi Timmcke; Valdemar Stajer; Sergej M. Ostojic (Elsevier, 2024)
Objectives: To assess the impact of medium-term supplementation with dihydrogen and pyrroloquinoline quinone (PQQ) on mitochondrial biomarkers, brain metabolism, and cognition in elderly individuals diagnosed with mild cognitive impairment. Design: A parallel-group, randomized, placebo-controlled, double-blind experimental design, maintaining a 1:1 allocation ratio between the experimental group (receiving the dihydrogen-producing minerals and PQQ) and the control group (receiving the placebo) throughout the trial. Setting and participants: Thirty-four elderly individuals with mild cognitive impairment (mean age 71.9 ± 3.8 years; 28 females) voluntarily provided written consent to participate in this trial. Participants were assigned in a double-blind parallel-group design to receive either a dihydrogen-PQQ mixture (Alpha Hope®, CalerieLife, Irvine, CA) or placebo twice daily for a 6-week intervention period. Methods: The primary endpoint was the change in serum brain-derived neurotrophic factor (BDNF) from baseline to the 6-week follow-up; secondary outcomes included cognitive function indices, specific metabolites in brain tissue, brain oxygenation, and the prevalence and severity of side effects. Interaction effects (time vs. intervention) were evaluated using two-way ANOVA with repeated measures and Friedman's 2-way ANOVA by ranks, for normally distributed data with homogeneous variances and non-homogeneous variances, respectively. Results: Dihydrogen-PQQ resulted in a significant elevation in serum BDNF levels at the six-week follow-up (P = 0.01); conversely, no changes in BDNF levels were observed in the placebo group throughout the study duration (P = 0.27). A non-significant trend in the impact of interventions on BDNF levels was observed (treatment vs. time interaction, P = 0.14), suggesting a tendency for dihydrogen-PQQ to upregulate BDNF levels compared to the placebo. A significant interaction effect was observed for the Alzheimer's Disease Assessment Scale-Cognitive subscale (ADAS-Cog) scores in the orientation domain (P = 0.03), indicating the superiority of dihydrogen-PQQ over placebo in enhancing this cognitive aspect. Cerebral oxygenation saturation exhibited a significant increase following the administration of the dihydrogen-PQQ mixture, from 48.4 ± 7.2% at baseline to 52.8 ± 6.6% at 6-week post-administration (P = 0.005). In addition, brain N-acetyl aspartate levels significantly increased at seven out of thirteen locations post-intervention in participants receiving the mixture (P ≤ 0.05). Conclusions: Despite the limited number of participants included in the study for interpreting clinical parameters, the dihydrogen-PQQ mixture blend shows promise as a potential dietary intervention for enhancing mental orientation and brain metabolism in individuals with age-related mild cognitive decline.